Stakeholders' Responses to CSR Tradeoffs: When Other-Orientation and Trust Trump Material Self-Interest - Bridoux, Flore; Stofberg, Nicole; Den Hartog, Deanne (Frontiers in Psychology, 2016)
When investing in corporate social responsibility (CSR), managers may strive for a win-win scenario where all stakeholders end up better off, but they may not always be able to avoid trading off stakeholders' interests. To provide guidance to managers who have to make tradeoffs, this study used a vignette-based experiment to explore stakeholders' intention to associate with a firm (i.e., buy from or become an employee) that trades off CSR directed at the stakeholders' own group (self-directed CSR) and CSR directed at another stakeholder group (other-directed CSR). Results show that stakeholders were not systematically more attracted to a firm that favors their own group over another stakeholder group. Specifically, stakeholders' other-orientation moderated their reaction to tradeoffs: stakeholders higher on other-orientation were willing to forego some material benefits to associate with a firm that treated suppliers in developing countries significantly better than its competitors, whereas stakeholders lower on other-orientation were more attracted to a firm favoring their own stakeholder group. Other-orientation also moderated reactions to tradeoffs involving the environment, although high CSR directed at the environment did not compensate for low self-directed CSR even for stakeholders higher on other-orientation. Second, the vignette study showed that trust mediated the relationship between tradeoffs and stakeholders' reactions. The study contributes first and foremost to the burgeoning literature on CSR tradeoffs and to the multimotive approach to CSR, which claims that other motives can drive stakeholders' reactions to CSR in addition to self-interest. First, it provides further evidence that studying CSR tradeoffs is important to understand both (prospective) employees' and customers' reactions to CSR-related activities. Second, it identifies other-orientation as a motive-related individual difference that explains heterogeneity in stakeholders' reactions to CSR. These findings suggest several avenues for future research for organizational psychologists interested in organizational justice. Third, it investigates trust as a mediating mechanism. Fourth, it reveals differences in stakeholders' reactions depending on which other stakeholder group is involved in the tradeoff. For practice, the findings suggest that tradeoffs are important because they influence which stakeholders are attracted to the firm.